Genderisation of power-knowledge in Biobío justice system, Chile - Miranda Pérez, Fabiola Marisol.; Cabrera Morales, Natalia. (Universidade Federal de Santa Catarina, 2024)
This work deepens into the gender gaps existing in justice institutions, understanding them as power and knowledge disputing spaces. While the tendency of existing studies in Chile on the subject has been to use qualitative methodologies, our research uses detailed statistics to study the case of the Bío-Bío region. This analysis allows fine –and, at the same time, global– observation of different organizational dimensions that are structured by gender, which do not always act univocally. With this purpose, the ratio of men and women professionals of law and the psychosocial field that work in justice institutions in the region is analyzed. Also, the income level associated to their positions is observed.
Generización del poder-saber en la Justicia de Biobío, Chile
Generização do poder e saber na Justiça de Biobío, Chile
Keywords: Instituciones de justicia; Poder; Genero; Sueldos